2016
DOI: 10.1021/acs.macromol.6b01754
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling and Functionalization of Coupled Polyisobutylene via Alkoxybenzene Quenching

Abstract: During living polymerization of isobutylene, marginal conditions can lead to reaction of carbenium ions with exo-olefin and production of coupled polyisobutylene (PIB). When living PIB containing a coupled fraction is subjected to end-quenching with an alkoxybenzene compound in the presence of TiCl4, the coupling reaction is quantitatively reversed to form the two original chain ends, and the regenerated chains are observed to possess the desired alkoxyphenyl functionality. To demonstrate this phenomenon, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Based on our experience with decoupling of coupled PIB, we initially entertained the possibility that every isoprene unit might be cleaved prior to functionalization, yielding difunctional oligomers ( F n = 2) with M n equal to the isoprene equivalent weight of the starting butyl rubber plus the molecular weight of two quencher molecules. Since our products possessed M n s significantly greater than EW IP and a functionality greater than 2 in all cases, we concluded that the cation resulting from protonation of the IP unit of butyl rubber is sufficiently sterically unhindered to allow attack by the alkoxybenzene, and functionalization often occurs without an accompanying cleavage event for that unit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our experience with decoupling of coupled PIB, we initially entertained the possibility that every isoprene unit might be cleaved prior to functionalization, yielding difunctional oligomers ( F n = 2) with M n equal to the isoprene equivalent weight of the starting butyl rubber plus the molecular weight of two quencher molecules. Since our products possessed M n s significantly greater than EW IP and a functionality greater than 2 in all cases, we concluded that the cation resulting from protonation of the IP unit of butyl rubber is sufficiently sterically unhindered to allow attack by the alkoxybenzene, and functionalization often occurs without an accompanying cleavage event for that unit.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction represents a novel variation of Friedel‐Crafts alkylation chemistry in which a bulky carbenium ion, which is sterically incapable of alkylation, undergoes β‐cleavage to yield two smaller fragments that readily undergo alkylation. In our previous report we noted that high molecular weight PIB‐based copolymers, possessing bulky, main‐chain unsaturations similar to those found in coupled PIB, might be subjected to this novel cleavage/alkylation chemistry to produce difunctional telechelic or polyfunctional PIB chains without need for expensive or difficultly‐synthesized polyfunctional initiators . Furthermore, because the cleavage/alkylation reaction requires the same catalyst, i.e., a Lewis acid, which is used during cationic polymerization of the starting copolymer, this process could theoretically be performed in the same vessel subsequent to copolymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyisobutylene (PIB) has found widespread use as an additive in lubricating oils for internal combustion engines, specifically as a dispersant, due to its advantageous properties including a low glass transition temperature ( T g ), chemical, oxidative, and thermal stability, and ease of chemical modification . PIB succinimide (PIBSI) is a commercially produced PIB‐based dispersant commonly used in lubricating oils to maintain solubility of polyaromatic hydrocarbons (PAHs) (i.e., soot), which are produced from incomplete combustion of fuel and are carried into the lubricating oil when exhaust gases pass the piston rings .…”
Section: Introductionmentioning
confidence: 99%
“…The source and purity of purchased materials and the synthesis of 2-chloro-2,4,4-trimethylpentane (TMPCl) and 2,4dimethyl-1,3-pentadiene (DMPD) are provided in the SI. The synthesis of coupled PIB containing an endo-coupled fraction has been previously reported; 26 the coupled PIB used herein is the same as PIB 3 in the cited work.…”
Section: ■ Introductionmentioning
confidence: 99%